Motivations for using dietary supplements in elite ice hockey - controlling weight and enhancing performance - Christensen, S.; Gjelstad, A.; Björnsdottir, I.; Lauritzen, F. (Nutrients, 2024)
Background: Excessive or improper use of dietary supplements (DSs) by athletes may cause adverse effects, such as impaired performance or failing a doping test, making it important for athletes to mitigate risk and make well-informed choices when using supplements.